LAKE BASE URBAN RECREATION IN DHAKA METROPOLITAN AREA: HATIRJHEEL LAKE AS A POTENTIAL CASE - Hossain, Mohammad Ismail; Aziz Ansari, Mohammad Nayem; Saika, Ummeh (International Journal of Research -GRANTHAALAYAH, 2017)
The main objective of this paper is to investigate tourists’ perceptions of services delivered by Hatirjheel lake-based Holiday recreation site in Dhaka Metropolitan area. The six structural variables were tourists' expectation, perceived quality, perceived value, satisfaction, loyalty and complaint. A face-to-face survey was conducted with tourists who had stayed for at least one hour in the Lake. The overall assessment of tourist satisfaction is 4.27 and tourist loyalty is 4.66, which indicates that the respondents are satisfied with the Hatirjheel area. The results indicated that air quality; noise pollution and sanitation were more important varieties. Tourists were more satisfied with the scenic area capacity, air quality, noise pollution and sanitation; while they were less satisfied with water quality, convenient traffic and parking. The sustainability of the Hatirjheel lake holiday recreation depends on the management and environmental management; therefore, the analyses and compares both sides of the utilization of the lake: the demand and the offer.